THE GROWT OF DIATOM Skeletonema costatum (Greville) Cleve OF JEPARAâS ISOLATES CULTURES IN f/2 DAN CONWAY CULTURE - Armanda, Dian Triastari (BIOMA, 2013)
Skeletonema costatum (Greville) Cleve (Bacillariophyceae) is the unisel photosynthetic microalgaeâs diatom which has the silica as the main composition of its cell walls. Diatoms have some life phases that can be observed in its batch culture The purpose of this research is to study the population growth of the diatom Skeletonema costatum populations in the f/2 medium and Conway medium of the growth curve is formed. This study also aims to determine the generation time and instantaneous growth rate of this the diatom species in both medium, in order to know which one is more appropriate medium for Skeletonema costatum.The batch culture of S. costatum was applied at f/2 medium and Conway medium with three replications for 7x24 hours in a sterile condition. Environmental parameters (pH, salinity, and temperature of the medium) were measured periodically. The population growth of the culture reached the lag phase in the first 24 hours, the exponential phase in the second 24 hours, whereas the stationary phase was in the third 24 hours. The growth of S. costatum in both medium were not significantly different. Skeletonema costatum growth rate in f/2 medium were 0.0282 cells/hour and its generation time were 25.5420 hours. On the other hand, Skeletonema costatum growth rate in Conway medium were 0.0228 cells/hour and its generation time were 30.3728 hours. This study proved that the growth of Skeletonema costatum populations in f/2 medium and Conway medium tends to be similar (Sig. 0.325, Î± = .10).Keywords: Skeletonema costatum, f /2 medium, Conway medium, growth rate, generation time